Supporting young immigrants in their transition from school to work? A staff perspective on challenges of vocational integration classes - Hannes Reinke; Michael Goller (International Journal for Research in Vocational Education and Training (IJRVET), 2022)
Context: The implementation of successful measures to support immigrants' integration in cultural, social, and economic life can be considered as one of today's greatest challenges for many societies. This is especially true for adolescent immigrants who have not yet been able to finish education or gain qualifications relevant to joining the labour market. That is why many receiving countries have developed and implemented special programmes that aim at supporting immigrants' integration by facilitating their employability. Unfortunately, not much is known about the process of implementing these programmes or about how education systems, schools, and teachers are dealing with the new situation and target group. In this contribution, the implementation, development, and challenges of German Vocational Integration Classes (VIC), as an example of comparable programmes in the EU, are investigated to address this research gap. The paper considers the following exploratory research questions: (a) What challenges have been experienced by teachers and social workers in the implementation of VIC as well as in the integration of immigrants into the labour market in recent years? (b) How can these challenges be met in the long run and how should VIC be developed to better achieve its aims?~Methods: To answer these questions, a sequential qualitative study containing questionnaire and interview elements was conducted. First, teachers and social workers involved in VIC filled in a questionnaire about their experiences and experienced challenges in implementing VIC (N = 46). Then, supplementing interviews were conducted with participants from the first sample in order to generate further insights and to contextualise the findings from the first study part (N = 14).~Findings: From the respondents' answers, it appears that the VIC programme is well implemented. The results show, however, that central challenges continue to exist. This concerns, for example, legal regulations or the development of adequate curricula, but also the scope and quality of language education. In addition, problems have also been identified with regard to students' culture-specific education and their individual attitudes. These prevailing problems seem to affect schooling and educational processes. In addition, respondents report feeling left alone to deal with problems and that their experiences from their daily work in VIC and with immigrants are not sufficiently taken into account in policy and school-related decisions.~Conclusions: Although VIC seems well implemented, key challenges remain in the view of the participants. It was found that teachers cannot solve many of the identified problems themselves, as they require action at the level of policy or school organisation. For staff, this can be accompanied by increased stress and demotivation. For the young immigrants, the existing challenges can have a long-term impact on school success and transition to vocational education and training. The study thus highlights the importance of targeted and holistic strategies to support immigrant integration through education.
Keywords: 330; Immigration; Educational Policy; Employability; Mixed Methods; VET; Vocational Education and Training; Transitions From Education and Training to Employment